INTERNET OF THINGS: A REVIEW ON THEIR REQUISITE IN THE DIGITAL ERA - S.Vanitha1*, P. Balasubramanie , K. S. Arvind , V.R.Niveditha , Saravanan Elumalai (International Journal of Advanced Science and Technology, 2020)
The Internet of Things is nothing but the amalgamation of connectivity between physical devices and daily objects. This technology empowers how computers can gather meaningful information in many ways, interconnect themselves with various enabling technologies like Artificial Intelligence, Big data Analytics, Cloud Computing and many more to track and count everything around us in their glory. It is also not surprising to note that IoT is considered to be one of the “Disruptive Technologies” with potential impacts in various fields like military, agriculture, medical, healthcare, industrial automation and smart living. This paper addresses the need for internet of things, their connecting devices, their architectures and popular frameworks and their application. Various visions of Internet of Things application has been reviewed and discussed in this paper. Furthermore, the shortcomings and research challenges in various applications have been deliberated in detail..